Role of the serum levels of the inter-organs messenger fibroblast growth factor 21 (FGF21) in the diagnosis and prognosis of breast cancer patients - Stella Maris Ranuncolo; Eduardo Armanasco; Myriam Nuñez; Laura Yuan; Sujhrob Makhkamov; Mariana S. De Lorenzo (Cell Communication and Signaling)
Abstract FGF21 regulates local and systemic metabolic homeostasis. High serum FGF21 was found in obesity, metabolic syndrome, type 2 diabetes mellitus, and coronary heart disease. The pathways linking obesity and breast cancer remain elusive. We aimed to analyze the serum FGF21 in breast cancer patients at diagnosis. Circulating FGF21 levels in 45 breast cancer women (median age 59, range 32–88 years) and 51 age-matched healthy controls were evaluated using a quantitative ELISA assay. Patients’ samples were obtained before surgery ahead of any previous therapy. Breast cancer patients showed significantly elevated serum FGF21 (median 267.13, range 28.41-780.45) respect to healthy controls (76.86, 0.00-425.60) (p < 0.0001). A ROC curve determined a cut-off value of 130.64 pg/ml to define positive or high FGF21 levels. Based on this cut-off point, 30/45 (66.7%) breast cancer patients showed positive serum FGF21 levels as compared to 18/51 (35.3%) healthy controls. Circulating FGF21 levels could be useful as a highly sensitive diagnosis biomarker for early breast cancer detection. We did not find any significant association between the serum FGF21 levels, and many clinical-pathological or metabolic parameters determined at the diagnosis of the primary disease. Interestingly, a statistically significant correlation was determined between serum FGF21 and the body mass index (BMI). Furthermore, patients with positive FGF21 serum levels had a worst overall survival (Log Rank Test [Mantle Cox] p = 0.017). We propose serum FGF21 levels determined at the diagnosis of primary breast cancer as a promising diagnostic and prognosis biomarker in this oncological disease.